Effect of Temperature and Time on the Penetration Layer of Pin Shaft in Vacuum Chromvanadizing - Chen Jiang; Mengjiu Zhang; Lishan Jin; Ningning Pang (Jixie chuandong)
As a very important part of the chain drive system， the sliding friction between the pin shaft and the sleeve will produce wear and tear during the operation， which will lead to the chain elongation failure to a certain extent. In view of this failure form， the surface of the pin shaft is treated with chromvanadizing to improve its surface hardness and then improve the wear resistance of the pin shaft. Through experiments， the influence of different temperatures and time on the penetration layer is studied to improve the quality of the infiltration layer， thus greatly improving the wear resistance of the chain.